A case of pigmented, free-floating vitreous cyst treated with micropulse diode laser - Gülkılık, Gökhan; Odabaşı, Mahmut; Erdur Karaman, Sevil; Özsütcü, Mustafa; Eliaçık, Mustafa; Demirci, Göktuğ; Kocabora, Mehmet Selim (Wiley-Blackwell, 2016)
Vitreous cysts, unattached to the retina, are rare findings that can be congenital or acquired.1 Although controversy exists, congenital vitreous cysts are usually nonpigmented and are believed to originate from the hyaloid vascular system.2 In contrast, acquired cysts usually have pigmented surfaces and are thought to arise from the iris or ciliary body pigment epithelium, which then dislodges into the vitreous either spontaneously or after blunt trauma.3 These cysts are usually asymptomatic and treatment is unnecessary. Argon laser or neodymium: yttrium aluminium garnet (Nd:YAG) laser photocystotomy and cyst removal with pars plana vitrectomy (PPV) have been described for the treatment of symptomatic cysts.4–6 We describe herein the first reported treatment of a pigmented, free-floating, vitreous cyst using a micropulse diode laser.
WOS: 000370485800015
PubMed ID: 26875859
Keywords: Laser; Low Vision; Retina; Citreous Cyst